What Can Cultural and Creative Industries Do for Urban Development? Three Stories from the Postsocialist Industrial City of Ostrava - Slach, Ondřej; Boruta, Tomáš (Quaestiones Geographicae, 2012)
This paper is focused on the role of cultural and creative industries in the regeneration of the inner city of Ostrava. The first part outlines the basic relationship of cultural and creative industries and urban areas in market economies, with emphasis on industrial cities. Ostrava is a post-socialist city, therefore essential characteristics of one are briefly given. The empirical part presents three case studies demonstrating the impact of cultural and creative industries on the regeneration of the inner city of Ostrava. In the conclusion, the case studies are discussed in a comparative perspective with special accent on the role of the public sector as an actor of culture-led regeneration in Ostrava.